Exenatide Once Weekly for Management of Type 2 Diabetes: A Review - Inaishi J; Saisho Y (Dove Medical Press, 2022)
Jun Inaishi,1,2 Yoshifumi Saisho1 1Division of Endocrinology, Metabolism and Nephrology, Department of Internal Medicine, Keio University School of Medicine, Tokyo, Japan; 2Center for Preventive Medicine, Keio University School of Medicine, Tokyo, JapanCorrespondence: Yoshifumi Saisho, Division of Endocrinology, Metabolism and Nephrology, Department of Internal Medicine, Keio University School of Medicine, 35 Shinanomachi, Shinjuku-ku, Tokyo, 160-8582, Japan, Tel +81-3-3353-1211 (x62383), Fax +81-3-3359-2745, Email ysaisho@keio.jpAbstract: Exenatide is one of the exendin-based glucagon-like peptide 1 receptor agonists (GLP-1RAs) and is currently available in two formulations, ie, exenatide twice daily (BID), a short-acting GLP-1RA, and exenatide once weekly (QW), a long-acting GLP-1RA. Clinical efficacy and safety of exenatide 2 mg QW in patients with type 2 diabetes (T2DM) has been demonstrated in the DURATION study program. Exenatide QW has been shown to achieve greater HbA1c reduction compared with exenatide BID, with less injection frequency and greater treatment satisfaction. However, exenatide QW failed to show a significant cardiovascular risk reduction in a cardiovascular outcome trial (CVOT), the EXSCEL trial, while other GLP-1RAs have shown positive CV outcomes. Furthermore, exenatide QW has been shown to be inferior to liraglutide and semaglutide with respect to HbA1c or body weight reduction in the head-to-head trials. Thus, although the long-term efficacy and safety of exenatide QW have been demonstrated, exenatide QW might be selected with lower priority within the class of GLP1-RAs for the management of T2DM, especially for patients at high CV risk. On the other hand, exenatide QW is now expected to be a treatment option for children with T2DM or patients with Parkinson's disease. This review provides an overview of the current evidence regarding the clinical efficacy and safety of exenatide QW and discusses the current perspectives on exenatide QW for treatment of T2DM.Keywords: exenatide once weekly, GLP-1 receptor agonist, type 2 diabetes, cardiovascular outcome